2018
DOI: 10.1515/joc-2018-0033
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement of HAP-Based Relaying M-PPM FSO System Using Spatial Diversity and Heterodyne Detection Receiver

Abstract: In this paper, we investigate the performance of a high-altitude platform (HAP)-based relaying free-space optical communication (FSO) system, where HAP plays a role as a relay node that employs detect-and-forward relaying scheme to connect between two ground stations (GSs). $M$-ary pulse-position modulation (PPM), spatial diversity, and heterodyne detection receiver are used to improve the system’s performance. Instead of using multiple-input multiple-output (MIMO), which makes the HAP complex, multiple-input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The impact of environmental and FSO communication system's parameters and their optimization need to be investigated accurately to address challenges effectively and ensure maximized link availability. Recent studies have demonstrated the advantageous impact of spatial diversity techniques on enhancing the performance of FSO links, particularly in the context of HAPS-assisted FSO communication systems [31]- [33]. In [31], the BER performance of HAPS-assisted FSO communication system was investigated considering the impact of both attenuation and atmospheric turbulence.…”
Section: B Haps Based Mimo Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of environmental and FSO communication system's parameters and their optimization need to be investigated accurately to address challenges effectively and ensure maximized link availability. Recent studies have demonstrated the advantageous impact of spatial diversity techniques on enhancing the performance of FSO links, particularly in the context of HAPS-assisted FSO communication systems [31]- [33]. In [31], the BER performance of HAPS-assisted FSO communication system was investigated considering the impact of both attenuation and atmospheric turbulence.…”
Section: B Haps Based Mimo Applicationsmentioning
confidence: 99%
“…Recent studies have demonstrated the advantageous impact of spatial diversity techniques on enhancing the performance of FSO links, particularly in the context of HAPS-assisted FSO communication systems [31]- [33]. In [31], the BER performance of HAPS-assisted FSO communication system was investigated considering the impact of both attenuation and atmospheric turbulence. Notably, the effect of pointing error was not incorporated in this particular study.…”
Section: B Haps Based Mimo Applicationsmentioning
confidence: 99%
“…The benefit of spatial diversity technique on the performance of FSO links has also been shown recently for HAPS-aided FSO communication systems in several studies [25], [26], [27]. In [25], the BER performance of HAPS-assisted FSO communication system was analyzed considering both attenuation and atmospheric turbulence. The effect of pointing error was not included in this study.…”
mentioning
confidence: 90%
“…Diversity is a widely used and efficient technique for improving performance of communication systems. System performance for outage probability and BER when using different diversity techniques are given in [15–18].…”
Section: Introductionmentioning
confidence: 99%